Efficient narrowband interference cancellation in ultra‐wide‐band rake receivers. Issue 1 (1st January 2013) - Abedi, Omid; Yagoub, Mustapha C.E.
Abstract : In this study, different pulse modulation parameters, such as symbol error rate (SER), power loss and bandwidth were investigated to highlight the most suitable parameter for narrowband interference cancellation in ultra‐wide‐band (UWB) Rake receivers. Thus, the performance of transmitter pulse was evaluated at the UWB Rake receiver. Finally, comparison of various filter bank receivers in terms of number of filters and SER was achieved by using a new accurate indoor UWB IEEE model channel with different propagation scenarios.